Critical temperature requirement for the germination and establishment of mungbean (Vigna radiata L.) in temperate environments - Silwal, Sachesh; Delahunty, Audrey J.; Wallace, Ashley J.; Norton, Sally; Pang, Alexis; Nuttall, James G. (Frontiers in Plant Science, 2026)
Mungbean (Vigna radiata (L.) R.Wilczek.) is an important annual legume cultivated in subtropical regions for its high-protein grains. However, it is susceptible to low temperatures (<20°C) during germination and establishment, which results in substantial yield loss. Early growth stages are crucial for successful cultivation in cooler climates to enable an optimal sowing window and effective establishment. This study aimed to identify cold-tolerant mungbean genotypes adapted to low-temperature germination (<20°C), particularly in southern Australia during November-December. The effects of temperature (14, 17 and 20°C) and soil water availability (40 and 80% of field capacity) on the germination and emergence of mungbean genotype were investigated through three experiments. In Experiment 1, thirty-two genotypes were evaluated for germination at constant temperatures of 14, 17 and 20°C using germination paper towels in a controlled environment. Additionally, in Experiment 2 and 3 in controlled environment experiments using soil-filled pots were conducted to determine the effect of temperature under constant (14, 17, and 20°C) and a range of diurnal temperature regimes (10–18°C, 13–21°C, and 16–24°C), ensuring that the average temperature for each treatment remained at 14, 17, and 20°C respectively. These temperatures were tested in factorial combination with soil water status (40 and 80% of field capacity) on the germination and emergence of commercial varieties Jade-AU and Celera II-AU. Germination occurred at all tested temperatures, with the highest germination percentage observed at 20°C on paper towels. Genotypes Putland, Jade-AU, Bari Mung-3, Bari Mung-4, Satin II, and Bina Mung-8 showed no significant differences in germination rates among the 14, 17, and 20°C temperature treatments, with average germination percentages exceeding 80% in the paper-towel evaluation. The median germination rate observed was highly variable (2–16 days) across genotypes in response to temperature treatment. The estimated base temperature of Celera II-AU and Jade-AU was 8.6 and 9.8°C, respectively. Seedling emergence was faster and higher for Celera II-AU than Jade-AU across the diurnal and constant temperatures. The germination was observed at both diurnal and constant temperature treatments of 20, 17, and 14°C. However, no emergence was observed at a constant temperature of 14°C for varieties Jade-AU and Celera II-AU. These findings suggest that mungbean can be successfully sown in early spring of southern Australia if soil temperature is at least 17°C. This research provides valuable insights for future breeding programs, germination studies, and sowing date recommendations in temperate environments.